2015
DOI: 10.1111/1750-3841.12871
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Enteric Viruses and Microbial Indicators in the Eastern Oysters (Crassostrea virginica) and Harvest Waters along Louisiana Gulf Coast

Abstract: Noroviruses are the most common causative agent of viral gastroenteritis in humans, and are responsible for major foodborne illnesses in the United States. Filter-feeding molluscan shellfish exposed to sewage-contaminated waters bioaccumulate viruses, and if consumed raw, transmit the viruses to humans and cause illness. We investigated the occurrence of norovirus GI and GII and microbial indicators of fecal contamination in the eastern oysters (Crassostrea virginica) and water from commercial harvesting areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…E. coli has been isolated from bivalve mollusks in different studies in Santa Catarina coast in Brazil (Pereira, Nunes, Nuernberg, Schulz, & Vieira Batista, ; Ramos et al, ) and in other states in Brazil (Forcelini, Kolm, & Absher, ; Ribeiro et al, ). In the United States, Montazeri et al () reported E. coli isolated from oysters. However, no study was conducted to characterize E. coli recovered from mollusks by genotypic and phenotypic methods in the United States and in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli has been isolated from bivalve mollusks in different studies in Santa Catarina coast in Brazil (Pereira, Nunes, Nuernberg, Schulz, & Vieira Batista, ; Ramos et al, ) and in other states in Brazil (Forcelini, Kolm, & Absher, ; Ribeiro et al, ). In the United States, Montazeri et al () reported E. coli isolated from oysters. However, no study was conducted to characterize E. coli recovered from mollusks by genotypic and phenotypic methods in the United States and in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli has been isolated from bivalve mollusks in different studies in Santa Catarina coast in Brazil (Pereira, Nunes, Nuernberg, Schulz, & Vieira Batista, 2006;Ramos et al, 2012) and in other states in Brazil (Forcelini, Kolm, & Absher, 2013;Ribeiro et al, 2016). In the United States, Montazeri et al (2015) reported E. coli isolated from oysters.…”
mentioning
confidence: 99%